Interaction enhanced imaging of Rydberg P states: preparation and detection of Rydberg atoms for engineering long-range interactions - Gavryusev, Vladislav; Ferreira Cao, Miguel; Kekić, Armin; Zürn, Gerhard; Signoles, Adrien (European physical journal special topics, 2016)
The Interaction Enhanced Imaging technique allows to detect the spatial distribution of strongly interacting impurities embedded within a gas of background atoms used as a contrast medium [1]. Here we present a detailed study of this technique, applied to detect Rydberg P states. We experimentally realize fast and efficient three-photon excitation of P states, optimized according to the results of a theoretical effective two-level model. Few Rydberg P-state atoms, prepared in a small cloud with dimensions comparable to the blockade radius, are detected with a good sensitivity by averaging over 50 shots. The main aspects of the technique are described with a hard-sphere model, finding good agreement with experimental data. This work paves the way to a non-destructive optical detection of single Rydberg atoms with high spatial and temporal resolution.
Gesehen am 14.05.2020